Congenital Pseudarthrosis of the Clavicle Joint and its impact on sports participation – Description of 2 Cases: diagnosis and treatment - Bielak, Maciej; Bielak, Ryszard; Kędra, Kamila; Michalik, Izabela; Zarańska, Julia; Aab, Arkadiusz; Bielak, Karolina (Journal of Education, Health and Sport, 2023)
Congenital Pseudarthrosis of the Clavicle (CPC) is a rare condition stemming from incomplete clavicular ossification nuclei fusion. Our work discusses CPC’s history, etiology, clinical features, and methods of therapy. We especially emphasize athletes affected by this condition. Here we presents two clinical cases, treatment approaches and outcomes. CPC’s distinct presentation, often painless, with central clavicular discontinuity and swelling, allows to differentiate it from other conditions. However, in sport athletes, due to the significant physical exertion involved, symptoms can manifest. Accurate diagnosis is crucial for effective management.